Hambatan-hambatan Komunikasi yang Dirasakan Peternak dalam Pembinaan Budidaya Sapi Potong di Kabupaten Ogal Ilir - E. Rosana; A. Saleh; Hadiyanto . (Institut Pertanian Bogor, 2010)
Effective communication can influence receiver attitude in order to accept innovation while its effectivity will declineby various factors. This research designed to describe individual characteristics and communication activities,communication barriers of cattle farmer in Ogan Ilir District, to analyze correlation of individual characteristics andcommunication activity to communication barrier and to analyze correlation between individual characteristics tocommunication activity of cattle farmer in Ogan Ilir Regency. The results were 1) Cattle farmers individualcharacteristics generally middle aged, elementary school graduated, low income, less experienced in cattle raising,low cosmopolite and good knowledge of cattle raising. While highest score in communication activity werecommunication methods, followed by group engagement, communication direction, communication intensity andinformation seeking respectively, 2) the most communication barrier felt by farmers are attention and friendliness,followed by prejudice, expectation gap and needs gap, 3) Generally, there was significant correlation betweenindividual characteristics to communication barrier for experience, cosmopolite and knowledge level, 4) there wassignificant correlation between communication activity to communication barriers and 5) generally, there wassignificant correlation between individual characterstics with communication activity for age, education, income,experience, cosmopolite and knowledge level. Based on the result, it was concluded that there was significantcorrelation between farmer factor and communication activity to communication barrier in order to improveproductivity cattle farmers in Ogan Ilir Regency.